Do the supply of and demand for rural public service facilities match? Assessment based on the perspective of rural residents. (July 2022) - Cui, Xijuan; Ma, Libang; Tao, Tianmin; Zhang, Wenbo
Highlights: Use UNA toolkit to objectively reflect the actual travel range of rural residents. Considering the number and type of facility availability and accessibility across different modes of travel Pay more attention to the differentiated needs of rural residents for a variety of facilities Abstract: The allocation of public service facilities is a game between social justice and a humanistic care value orientation. Under the background of China's rural revitalisation strategy, the spatial configuration of rural public service facilities pays more attention to the personalised needs of rural residents, the main user, based on the previous spatial layout. In this study, we constructed a theoretical framework for the allocation priority of public service facilities, from the perspective of rural residents; this can be used in the allocation planning of rural public service facilities. The aims of this study were to measure the supply of and demand for various rural public service facilities and explore the configuration priority of various rural public service facilities. To this end, we used the 207 villages in Longxi County in the Longzhong Loess Hilly Region as an example, based on the classification of the supply and demand factors of rural public service facilities, and applied the Urban Network Analysis Toolbox (UNA) toolkit and demand intensity measurement methods. The results indicated that (1) the number and spatial distribution of various types of rural public service facilities were uneven, with the township as the centre and a multi-node clustered distribution. (2) Under different travel modes, there were obvious differences in the number and types of rural public service facilities, and the SC(shopping consumption) and CL(convenience life) lacking classes were higher than SL(sports and leisure) and SECH(science, education, culture, and health). (3) The total demand for rural public service facilities was significantly different (0.4–4), and the demand for CL was the highest. (4) Under different travel conditions or even under the same travel mode, there were obvious differences in the supply of and demand for rural public service facilities. In the context of rural revitalisation, the combination of standardisation, pertinence, differentiation, and balance, helps orderly allocate rural public service facilities, improves the rural living environment, and promotes the space of and social equality in rural public service facilities.